Pengaruh Bauran Pemasaran (7P) terhadap Keputusan Berbelanja di Swalayan - Rinaldi, Udin (Universitas Brawijaya, Indonesia, 2009)
Research target is to know influence in simultaneous and partial from marketing mix variable consist of product, price, place, promotion, people, physical evidence, and process to decision of consumer purchasing, and to know marketing mix variable that have an effect on dominantly. The result of research finds that in simultaneous accept hypothesis with f-count 9,035 bigger than f-tables (9,035 > 2,10), concluded existence of influence from marketing mix to decision of consumer purchasing. In partial accept hypothesis for each marketing mix variable consist of price variable, process, product, promotion, and physical evidence. Meanwhile place variable and people show weak influence.